Humanoid Robot-Application and Influence - Choudhury, Avishek; Li, Huiyan; Greene, Christopher M; Perumalla, Sunanda (Archives of Clinical and Biomedical Research, 2018)
Application of humanoid robot have been widely used in the field of healthcare and education. It has been recurrently used to improve social behavior and mollify distress level among children with autism, cancer and cerebral palsy. This article discusses the same from a human factors’ perspective. It shows how people of different age and gender have a different opinion towards the application and acceptance of humanoid robots. Additionally, this article highlights influence of cerebral condition and social interaction on a user’s behavior and attitude towards humanoid robots. Our study performed literature review and found that: (a) children and elderly individuals prefer humanoid robots due to inactive social interaction; (b) The deterministic behavior of humanoid robots can be acknowledged to improve social behavior of autistic children; (c) Trust on humanoid robots is highly driven by its application and a user’s age, gender and social life.